Avaliação da performance de medição de gás úmido pela tecnologia de cone invertido por ciência de dados - Lima, Phelipe Augusto Santos Oliveira (2024)
A particular case of multiphase Cows is that of wet gas, which is present in various industrial sectors such as power generation, the food industry, chemicals, and primarily in the oil and gas industry. Monitoring this Ćow is of utmost importance to meet not only legal requirements but also production outlook and the design and development of new techniques to enhance well efficiency. It is known that the presence of water at high Gas Volume Fractions, in other words, in wet gas conditions, leads to an overreading tendency in measurements by differential pressure meters. Therefore, being a low-cost technology with a well-known physical principle, the use of these meters for wet gas applications is gaining prominence in the industry. Inverted cone meters are the most recent technology in differential pressure Ćow measurement, standing out for their low pressure drop and the requirement for shorter straight pipe lengths when compared to oriĄce plates. Therefore, considering the applicability of statistical inference techniques and the data processing capabilities of data science for multidimensional data, the implementation of various techniques becomes one of the possible tools for assessing the performance of two-phase Ćows. The experimental results obtained indicate a linear relationship between overreading, pressure, and the dimensionless Lockhart-Martinelli parameter. The methodology of this work aims to contribute to the implementation of new techniques for correcting overreading in two phase Ćows.